2009
DOI: 10.4088/jcp.08m04839
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlates of Inappropriate Pediatric Psychiatric Emergency Room Visits

Abstract: Over one third of PPERS visits were inappropriate, characterized by better functioning, low harm potential or severity of presenting complaint, and absent suicidality or psychosis. Development of and improved access to urgent child and adolescent psychiatric outpatient care services in the community and referral agent educational programs may minimize inappropriate PPERS visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 0 publications
4
37
2
2
Order By: Relevance
“…In contrast with other studies (Edelsohn et al, 2003;Soto et al, 2009) no indication was found for the MCT of becoming the primary means of obtaining Child Care in Practice 265 mental healthcare, following non-urgent visits. Instead, the MCT offers service to a most challenging group of youngsters with severe problems.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In contrast with other studies (Edelsohn et al, 2003;Soto et al, 2009) no indication was found for the MCT of becoming the primary means of obtaining Child Care in Practice 265 mental healthcare, following non-urgent visits. Instead, the MCT offers service to a most challenging group of youngsters with severe problems.…”
Section: Discussioncontrasting
confidence: 81%
“…As such, Edelsohn, Braitman, Rabinovich, Sheves, and Melendez (2003) found that 40% of visits to a paediatric PES were non-urgent, suggesting a largely unmet mental healthcare need among children and adolescents from regular care providers. Soto et al (2009) also found a high number (over one-third) of inappropriate visits to a paediatric psychiatric emergency room, characterised by low severity of the presenting complaint. Consequently, they point to the need for the development of and improved access to urgent psychiatric care for children and adolescents in community-based outpatient care services, as well as referral agent educational programmes.…”
mentioning
confidence: 93%
“…With no clarity on adult ASD treatment guidelines and possible delayed/foregone care due to low access to services in many states/regions may put adults with ASD at a substantial risk of high ED use and costs. Our hypothesis is also supported by other studies (Williams et al 2001, Soto et al 2009) which have shown that strong predictors of frequent and inappropriate ED use among individuals needing psychiatric care include lack of a coordinated community program for mental health and outpatient psychiatric services that can provide timely care to individuals with psychiatric disorders such as ASD. Studies have also underlined that many such psychiatric ED cases could have been handled well in an outpatient primary setting due to the non-urgent nature of the complaint (Sills and Bland, 2002; Soto et al 2009).…”
Section: Paucity Of Trained Professionalssupporting
confidence: 84%
“…Our hypothesis is also supported by other studies (Williams et al 2001, Soto et al 2009) which have shown that strong predictors of frequent and inappropriate ED use among individuals needing psychiatric care include lack of a coordinated community program for mental health and outpatient psychiatric services that can provide timely care to individuals with psychiatric disorders such as ASD. Studies have also underlined that many such psychiatric ED cases could have been handled well in an outpatient primary setting due to the non-urgent nature of the complaint (Sills and Bland, 2002; Soto et al 2009). The Emergency Medical Treatment and Labor Act (EMTALA) (Zibulewsky, 2001), whereby in the US any patient requesting examination/treatment for any health condition must be provided with medical/psychiatric evaluation in an emergency situation, many a time makes ED a source of primary care for those with psychiatric needs such as ASD in absence of other mental health facilities in the region.…”
Section: Paucity Of Trained Professionalssupporting
confidence: 84%
“…Researchers have explored how factors of posttraumatic symptoms may influence each other longitudinally (Marshall, Schell, Glynn, & Shetty, 2006; Pietrzak et al, 2014; Schell, Marshall, & Jaycox, 2004; Solberg, Birkeland, Blix, Hansen, & Heir, 2016; Solomon, Horesh, & Ein-Dor, 2009). Common findings among these studies are that intrusive and hyperarousal symptoms predict further symptom development.…”
Section: Introductionmentioning
confidence: 99%